Dysregulation of memory B cells and circulating T follicular helper cells is a predictor of poor immune recovery in HIV‐infected patients on antiretroviral therapy. Issue 2 (16th February 2023) - Liu, Yan; Li, Zhen; Lu, Xiaofan; Kuang, Yi‐Qun; Kong, Deshenyue; Zhang, Xin; Yang, Xiaodong; Wang, Xiuwen; Mu, Tingting; Wang, Hu; Zhang, Yihang; Jin, Junyan; et al.
Abstract: T follicular helper (Tfh) cells and their interactions with B cells within the germinal center play extensive roles in human immunodeficiency virus (HIV) pathology. However, their association with immune reconstitution during antiretroviral therapy (ART) is still unclear. The aim of this study was to determine the impact of Tfh and memory B cell function on T helper cell recovery in patients with acute or chronic HIV infection. A total of 100 HIV‐infected individuals were enrolled in our study, classified into acute and chronic HIV infection groups (60 and 40, respectively), and subsequently classified into immunological responder (IR) and immunological nonresponder (INR) subgroups according to immune recovery outcomes after 96 weeks of ART. Liquid chromatography‐mass spectrometry was used to quantify the temporal regulation patterns of B and CD4 + T‐cell profiles among patients, and flow cytometry was used to investigate certain subsets of B and T cells. Here we showed that the prevalence of Tfh cells in the T helper cell population correlated negatively with CD4 + T‐cell recovery. The proportion of CXCR3 −  Tfh cells in patients with acute or chronic infection was associated with CD4 + T‐cell count recovery, and the proportion of CD21 + memory B cells at baseline was significantly higher in those with improved immune recovery outcomes. Universal proteomic dysregulation of B and CD4 + T cells at baseline was detected in patients with acute infected and poor CD4 + T‐cell recovery. Proteomics analysis revealed distinct temporal regulation profiles of both T helper cells and B cells between IRs and INRs among patients with acute infection. Our results suggest that the functions of memory B cells in INRs are dysregulated at the early stage of ART, possibly through disruption of Tfh cell function. The frequency and function of Tfh cells and their subsets are potential predictors of poor immune recovery.